TEM image simulation of silicon nitride using multislice technique - Thai, Connie Ker Nie. (2011)
In Transmission Electron Microscopy (TEM), high resolution images require comparison with simulated images as artifacts are usually generated experimentally. Hence, the objective of this project is to simulate TEM image of beta phase silicon nitride (β-Si3N4) by using multislice method and determine the dependency of image resolution on thickness and defocus values. The image simulated is assumed to be perfectly coherent. The β-Si3N4 supercell was constructed and each atom coordinates were measured prior to inputting data into simulation programs; namely the ATOMPOT, MULSLICE and IMAGE programs. These three programs were used to calculate atom potential, calculate mutlislice layers and generate images by adding the effects of objective lens aberrations respectively. By comparing simulation results with published works and varying of parameters, it is found that the β-Si3N4 image has optimum resolution at defocus value 700Å and specimen thickness of 2.906Å. At Scherzer defocus (700Å), the contrast transfer function (CTF) shows a broad transmittance band at negative value where positive phase contrast was formed. This resulted in the formation of dark and bright regions which indicates the presence atoms and channels respectively. Overfocus and underfocus occurs as image plane displace further from Scherzer defocus, resulted in a loss in sharpness and resolution. The point resolution under Scherzer condition is 2.4213Å, determined by the intersection of CTF on spatial frequency, k-axis. Besides, interference and diffraction on electron wave’s path that arise with increasing specimen thickness resulted in a decrease in image resolution. The amplitudes of all diffracted beams increase proportionally up to a certain thickness limit before the first maxima point appear. With the aid of simulation program, interpretation of experimental images can be carried out more easily.